Analysis of Financial Statement Fraud in the Perspective of Fraud Triangle Theory in Energy Companies - Nur Hidayatus Solikhah; Fadilla Cahyaningtyas (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2024)
This research aims to determine good corporate governance and ineffective monitoring of the condition of financial reports. This research uses a quantitative approach with a sample of 33 companies listed on the Indonesia Stock Exchange (IDX) for the period 2020 - 2022. This research investigates the relationship between the independent variable and the dependent variable by analyzing data from energy sector companies. This method uses multiple linear analysis techniques. The research results show that managerial ownership has a significant impact on the condition of financial statements. In line with the fraud triangle theory, which states that high management ownership can increase pressure to achieve financial goals and provide an opportunity to do so. Financial statement fraud is not influenced by institutional ownership and ineffective monitoring. These findings suggest that the effects of institutional ownership and ineffective monitoring may not be easy to predict. Further research is needed to understand the complexity of the components that contribute to the condition of financial statements.